Early childhood education of refugee students in Lebanon : teachers’ perspectives - Alhajji, Yehya (2020)
According to (International Rescue Committee, 2018), International Rescue Committee (IRC) is offering emergency services for about 1.5 Syrian refugees in Lebanon who fled their homelands since 2011. A large number of the refugee population are categorized as children under the age of 18. The small country Lebanon has been called to respond to this humanitarian crisis, and some non-governmental organizations (NGOs) responded to offer educational services for those children. Taking into account the increasing need for refugee education support and especially during the last few years, this study attempts to understand the integration process for refugee students into the Lebanese curriculum, through early childhood education, based on teachers’ perspectives. In this qualitative research, interviews were conducted with teachers who are directly contacting refugee students, within an early childhood education care (ECEC) program in January 2020 at three different schools in Northern of Lebanon. One of the NGOs in Lebanon provided the ECEC centres, and all the services were free of charge for refugees. The findings that were extracted from the interviews through content analysis, made it possible to explore the barriers that affect the learning process of refugee students. However, content analysis is a common methodology that is used to study cases in qualitative research. It helps to find out the meaning of text within the quantification of the meaning of spoken or written language (Renz et al, 2018). New methodologies will be mentioned in the study such as, the play-based environment that was used by teachers, to mitigate challenges in the classroom, and support children’s integration process in the Lebanese curriculum, and the motivation chains to which participants had access for academic and attitude cases within the ECEC classes. In addition, the findings denote the various issues and system interconnections that shape the reality facing refugees at local communities. There are techniques such as creativity, open discussions and dialogues that outline the integration process of refugee students, which challenges their learning, development processes, and overall academic experience. ECEC, however, could have a positive impact the children through the support that teachers received through training as well as the academic support by the NGO.